An Interior Inverse Problem with LocalDerivative - Khalili, Y.; Koyunbakan, H. (Pleiades Publishing Inc, 2025)
This paper is about a fractional Sturm-Liouville equation with conformable fractional derivative and spectral boundary conditions. We provide the uniqueness theorem for the conformable Sturm-Liouville operator's inverse problem solution using interior spectral data.
Keywords: interior inverse problem; conformable; Sturm-Liouville operator; spectrum